2017
DOI: 10.1158/1541-7786.mcr-17-0058
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity with NOTCH Inhibition and Androgen Ablation in ERG-Positive Prostate Cancer Cells

Abstract: The oncogenic activation of the ETS related gene (ERG) due to gene fusions is present in over half of prostate cancer (CaP) in Western countries. Due to its high incidence and oncogenic role, ERG and components of ERG network have emerged as potential drug targets for CaP. Utilizing gene expression datasets, from matched normal and prostate tumor epithelial cells, an association of NOTCH transcription factors with ERG expression status was identified; confirming that NOTCH factors are direct transcriptional ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…In addition, it was also suggested that HIF-1α may be a potential molecular target of PCa (43). The Notch signaling pathway was discovered to serve an important role in the PCa cell proliferation and apoptosis (44). Nevertheless, there are few studies focusing on the role of the Notch signaling pathway on the invasion and metastasis of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was also suggested that HIF-1α may be a potential molecular target of PCa (43). The Notch signaling pathway was discovered to serve an important role in the PCa cell proliferation and apoptosis (44). Nevertheless, there are few studies focusing on the role of the Notch signaling pathway on the invasion and metastasis of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Work by Mohamed and colleagues found GSI can synergize with enzalutamide, abiraterone, as well as another antiandrogen, bicalutamide to decrease cell proliferation, viability, and apoptosis of ERG-positive prostate cancer cells (VCaP), as Notch1 and 2 were found to be targets of ERG (39). ERG is an ETS family transcription factor commonly found increased in prostate cancer in roughly 50% of patients due to gene fusions with TMPRSS2 serine protease (40).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging strategies to inhibit ERG include direct as well as indirect targeting of ERG (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The ERG-targeted therapies include inhibition of the DNAbinding and transcription activator function of ERG, destabilization of ERG protein, inhibition of CaP-associated ERG mRNA, blocking direct ERG interacting co-activators or the simultaneous disruption of cooperating ERG upstream and downstream factors or its downstream signaling events, including NF-κB or NOTCH (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) April 30, 2018; DOI: 10.1158/0008-5472. CAN-17-2949 Taken together, ERG oncoprotein and the ERG network represent promising, however challenging targets for ERG positive CaP and other cancers.…”
Section: Introductionmentioning
confidence: 99%